Mappila: Identity and semantic narrowing - Joseph Koyippally Joseph
Mappila, the generic name for the Kerala-settled West Asian diaspora which gradually got integrated with the indigenous community, has undergone semantic narrowing to meanthe Muslims of North Kerala (Illias 436 fn. 4)since thetwentiethcentury. However, neither all Muslims of North Keralaare mappilas nor is North Kerala the only place of Muslim mappilas. Moreover, there are also non-Muslim mappilas in Kerala. The West Asian trade settlements which came up in the southern, central, and northern Kerala established communities in those regions through marital alliances with the local community, and are qualified by words referring to their religious affiliations such as ̳Jewish‘(Yuda mappila), ̳Christian‘ (Nasrani mappila) and ̳Muslim‘ (Jonaka mappila) (Malieckal 300; Županov 99).The meaning of the term got narrowed when the Muslim mappilas began asserting their identity due to political reasons that threatened their identity